'n Kruiskulturele ondersoek na Christelike moraliteit onder universiteitstudente - A. le Roux (Acta Theologica)
The world is currently experiencing a serious moral crisis. On the one hand, South Africa is considered one of the world’s most Christian societies, but on the other hand, it also has exceptionally high crime rates, in particular murder and rape, with HIV/AIDS growing at an alarming rate. As these factors are closely related to human morality, the researcher was interested in investigating the state of Christian morality on a South African campus. The moral values of students of two different culture groups at the University of the Free State were measured and compared. The results showed no significant difference between the moral values of black and white students. However, there was a very significant difference between male and female morality. The scores of the female students were significantly higher than those of the male students, implying that their Christian moral values are considerably stronger than those of their male counterparts.